Psychological intervention with female victims of natural disasters - Deza Villanueva, Sabina (2013)
We present the effects of disasters on mental health from a gender perspective, considering thatwomen are more vulnerable because they are more prone to damage, loss and suffering in thecontext of different threats, and generally also have less opportunity to access to material and socialresources. It also evidences how women assume various roles: as a victim, as the organizer ofremedial actions and in the prevention, mitigation and management of disasters. Finally it emphasizesthe need to train and enhance the skills of women in the management of emergency situationsas active agents in the prevention within their homes and communities, protecting mental health.